Production of phenylacetyl-homoserine lactone analogs by artificial biosynthetic pathway in Escherichia coli - Kang, Sun-Young (Microb Cell Fact, 2015)
BACKGROUND: Quorum sensing (QS) networks are more commonly known as acyl homoserine lactone (HSL) networks. Recently, p-coumaroyl-HSL has been found in a photosynthetic bacterium. p-coumaroyl-HSL is derived from a lignin monomer, p-coumaric acid, rather than a fatty acyl group. The p-coumaroyl-HSL may serve an ecological role in diverse QS pathways between p-coumaroyl-HSL producing bacteria and specific plants. Interference with QS has been regarded as a novel way to control bacterial infections. Heterologous production of the QS molecule, p-coumaroyl-HSL, could provide a sustainable and controlled means for its large-scale production, in contrast to the restricted feedback regulation and extremely low productivity of natural producers. RESULTS: We developed an artificial biosynthetic process for phenylacetyl-homoserine lactone analogs, including cinnamoyl-HSL, p-coumaroyl-HSL, caffeoyl-HSL, and feruloyl-HSL, using a bioconversion method via E. coli (CB1) in the co-expression of the codon-optimized LuxI-type synthase (RpaI) and p-coumaroyl-CoA ligase (4CL2nt). In addition to this, we show the de novo production of p-coumaroyl-HSL in heterologous host E. coli (DN1) and tyrosine overproducing E. coli (DN2), containing the rpaI gene in addition to p-coumaroyl-CoA biosynthetic genes. The yields for p-coumaroyl-HSL reached 93.4 ± 0.6 and 142.5 ± 1.0 mg/L in the S-adenosyl-l-methionine and l-methionine feeding culture in the DN2 strain, respectively. CONCLUSIONS: This is the first report of a de novo biosynthesis in a heterologous host yielding a QS molecule, p-coumaroyl-HSL from a glucose medium using a single vector system combining p-coumaroyl-CoA biosynthetic genes and the LuxI-type synthase gene. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0379-1) contains supplementary material, which is available to authorized users.